The Wigner transformation is of finite order - Várilly Boyle, Joseph C. (1987)
The Wigner integral transformation, which intertwines the twisted product and the composition of kernels, is of order 24. Indeed, it commutes with, and its sixth power equals, the Fourier cotransformation.